PENGARUH SALES GROWTH, LEVERAGE, ROA DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE DAN KEPEMILIKAN INSTITUSIONAL SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN SUB SEKTOR COAL MINING YANG TERDAFTAR PADA BEI PERIODE 2020-2022 - Herlina; Wirda Lilia; Gavin; Acai Sudirman (Journal Accounting International Mount Hope, 2024)
The purpose of this study is to analyze Sales Growth, Leverage, ROA and Company Size on Tax Avoidance and Institutional Ownership as moderating variables. The research method uses a quantitative approach. The population used in this study are companies listed on the coal mining index on the Indonesia Stock Exchange in the period 2020-2022. The data collection technique uses secondary data. The data analysis technique uses multiple linear regression analysis. The research sample obtained was 23 coal mining sub-sector companies with 69 observations. The results of the study obtained that Sales growth partially had a negative and significant effect on Tax Avoidance, leverage partially had a positive and significant effect on Tax Avoidance, ROA and company size partially did not affect Tax Avoidance. While simultaneously sales growth, leverage, ROA and company size had a positive and significant effect on Tax Avoidance. The results of the Institutional ownership purchase moderation test could not moderate the effect of sales growth, leverage, ROA and company size on Tax Avoidance.